The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/ncomms4348
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics supports baculoviruses as vectors of horizontal transfer of insect transposons

Abstract: Horizontal transfer (HT) of DNA is an important factor shaping eukaryote evolution. Although several hundreds of eukaryote-to-eukaryote HTs of transposable elements (TEs) have been reported, the vectors underlying these transfers remain elusive. Here, we show that multiple copies of two TEs from the cabbage looper (Trichoplusia ni) transposed in vivo into genomes of the baculovirus Autographa californica multiple nucleopolyhedrovirus (AcMNPV) during caterpillar infection. We further demonstrate that both TEs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 54 publications
5
93
1
1
Order By: Relevance
“…Although the vector of transfer remains unknown, an early study implicated a parasitic mite that feeds on the cytoplasm of early Drosophila embryos, potentially introducing foreign DNA into germline nuclei prior to cellularization (Houck et al 1991). This model is consistent with recent genomic analyses, which increasingly point to hostparasite interactions as vehicles for the horizontal transfer of TEs (Gilbert et al 2010(Gilbert et al , 2014Parisot et al 2014).…”
Section: Population Invasion and Horizontal Transfersupporting
confidence: 63%
“…Although the vector of transfer remains unknown, an early study implicated a parasitic mite that feeds on the cytoplasm of early Drosophila embryos, potentially introducing foreign DNA into germline nuclei prior to cellularization (Houck et al 1991). This model is consistent with recent genomic analyses, which increasingly point to hostparasite interactions as vehicles for the horizontal transfer of TEs (Gilbert et al 2010(Gilbert et al , 2014Parisot et al 2014).…”
Section: Population Invasion and Horizontal Transfersupporting
confidence: 63%
“…T. ni is a representative lepidopteran for studying fundamental insect physiology, biochemistry and molecular biology (Hanzlik & Hammock, ; Jones, Schelling, & Chhokar, ; Lam, McNeil, & Donly, ; Lundstrom, Liu, Kang, Berzins, & Steiner, ; Simmons, D'Souza, Rheault, & Donly, ; Wang & Granados, ). As a highly polyphagous noctuid generalist, T. ni has often been used for studying insect‐plant interactions, insect chemical ecology, insect‐microbe interactions and insect pathology (Bidart‐Bouzat & Kliebenstein, ; Fuxa, Richter, Ameen, & Hammock, ; Gilbert et al, ; Herde & Howe, ; Wang & Granados, ; Wang et al, ; Zeng, Wen, Niu, & Berenbaum, ). Trichoplusia ni has also been used as a herbovirous insect to investigate effects of environmental contanimants on agricultural ecosystems and to study tritrophic interactions among host plants, insects, and microbes (Haney et al, ; Pennington et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ivancevic et al (2013) showed that the LINE BovB has been horizontally transferred to several taxonomic groups as diverse as marsupials, ruminents, squamates or monotremes, through an arthropod vectors (ticks). Gilbert et al (2014) recently showed that two transposons (Mar1 and IFP2) initially found in the genome of the cabbage looper Trichoplusia ni, a moth feeding on a wide spectrum of plant species, could transpose in the genome of the baculovirus AcMNPV upon its infection of the insect. The low frequency of transposition events together with the polymorphisms of insertions sites in the 240-kbp viral genome strongly suggests that the transposition of these two families occurred very recently, which leads to hypothesize that the HTTs are concommittent with viral infection.…”
Section: Mechanisms Of Httsmentioning
confidence: 99%